Will Proton Pump Inhibitors Increase the Risk of Diabetes Mellitus? A Systemic Review and Meta-Analysis - Chen, Yue; Hu, Lei; Sun, Chenyu; Bao, Jiantong; Liu, Jie; Bhan, Chandur; Kim, Keun Young; Manem, Raveena; Thapa, Pratikshya; Ma, Shaodi; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Proton pump inhibitor use was reported to potentially provide benefits to prevent diabetes mellitus. This study aims to investigate the association between proton pump inhibitor use and the risk of developing diabetes mellitus. Methods: This study was registered on the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42021238481). A systematic literature search was conducted to identify eligible studies up to February 2021. Quality assessment was conducted according to Jadad Scoring Scale and Newcastle–Ottawa Scale. The heterogeneity among studies was tested and estimated by Q test and I2. Pooled hazard ratio with 95% CI was calculated using the random-effects or fixed-effects model depending on the heterogeneity. Subgroup analyses, sensitivity analysis, and publication bias assessment were also performed. Results: Eight studies including 850 019 participants were included. We found that proton pump inhibitor use was associated with a statistically non-significant increased risk of diabetes mellitus (pooled hazard ratio was 1.06, 95% CI = 0.89-1.28, P = .50). In subgroup analysis, 5 studies conducted in North America confirmed the overall result; however, one study conducted in Europe demonstrated a statistically significant increased risk, while one study in Asia revealed a statistically significant decreased risk. Conclusion: Proton pump inhibitor use is not associated with either increased or decreased risk of diabetes mellitus. However, more well- designed studies focusing on proton pump inhibitor use and the risk of diabetes mellitus, especially among populations with different backgrounds, are still needed.